Association of Pretreatment Hippocampal Volume With Neurocognitive Function in Patients Treated With Hippocampal Avoidance Whole Brain Radiation Therapy for Brain Metastases: Secondary Analysis of NRG Oncology/RTOG 0933 - Christopher D. Abraham, MD; Stephanie L. Pugh, PhD; Joseph A. Bovi, MD; Vinai Gondi, MD; Minesh P. Mehta, MD; Tammie Benzinger, MD; Christopher J. Owen, MS; Simon S. Lo, MD; Vijayananda Kundapur, MD; Paul D. Brown, MD; Alexander Y. Sun, MD; Steven P. Howard, MD; et al. (Advances in Radiation Oncology, 2022)
Purpose: Hippocampal volume (HV) is an established predicting factor for neurocognitive function (NCF) in neurodegenerative disease. Whether the same phenomenon exists with hippocampal-avoidant whole brain radiation therapy is not known; therefore, we assessed the association of baseline HV with NCF among patients enrolled on RTOG 0933. Methods and Materials: Hippocampal volume and total brain volume were calculated from the radiation therapy plan. Hippocampal volume was correlated with baseline and 4-month NCF scores (Hopkins Verbal Learning Test–Revised [HVLT-R] Total Recall [TR], Immediate Recognition, and Delayed Recall [DR]) using Pearson correlation. Deterioration in NCF was defined per the primary endpoint of RTOG 0933(mean 4-month relative decline in HVLT-R DR). Comparisons between patients with deteriorated and nondeteriorated NCF were made using the Wilcoxon test. Results: Forty-two patients were evaluable. The median age was 56.5 years (range, 28-83 years), and 81% had a class II recursive partitioning analysis. The median total, right, and left HVs were 5.4 cm3 (range, 1.9-7.4 cm3), 2.8 cm3 (range, 0.9-4.0 cm3), and 2.7 cm3 (range, 1.0-3.7 cm3), respectively. The median total brain volume was 1343 cm3 (range, 1120.5-1738.8 cm3). For all measures of corrected HV, increasing HV was associated with higher baseline HVLT-R TR and DR scores (ρ: range, 0.35-0.40; P-value range, .009-.024) and 4-month TR and DR scores (ρ: range, 0.29-0.40; P-value range, .009-.04), with the exception of right HV and 4-month DR scores (ρ: 0.29; P = .059). There was no significant association between HV and NCF change between baseline and 4 months. Fourteen patients (33.3%) developed NCF deterioration per the primary endpoint of RTOG 0933. There was no significant difference in HV between patients with deteriorated and nondeteriorated NCF, although in all instances, patients with deteriorated NCF had numerically lower HV. Conclusions: Larger HV was positively associated with improved performance on baseline and 4-month HVLT-R TR and DR scores in patients with brain metastases undergoing hippocampal-avoidant whole brain radiation therapy but was not associated with a change in NCF.